Creating a Culture of Health in Planning and Implementing Innovative Strategies Addressing Non-communicable Chronic Diseases - Tziraki-Segal, Chariklia; De Luca, Vincenzo; Santana, Silvina; Romano, Rosa; Tramontano, Giovanni; Scattola, Paola; Celata, Corrado; Gelmi, Giusi; Ponce Márquez, Sara; Lopez-Samaniego, Luz; Zavagli, Veronica; Halkoaho, Arja; et al. (Frontiers in Sociology, 2019)
Ongoing demographic changes are challenging health systems worldwide especially in relation to increasing longevity and the resultant rise of non-communicable diseases (NCDs). To meet these challenges, a paradigm shift to a more proactive approach to health promotion and maintenance is needed. This new paradigm focuses on creating and implementing an ecological model of Culture of Health. The conceptualization of the Culture of Health is defined as one where good health and well-being flourish across geographic, demographic, and social sectors; fostering healthy equitable communities where citizens have the opportunity to make choices and be co-producers of healthy lifestyles. Based on Antonovsky’s Salutogenesis model which asserts that the experience of health moves along a continuum across the lifespan, we will identify the key drivers for achieving a Culture of Health. These include mindset/expectations, sense of community, and civic engagement. The present article discusses these drivers and identifies areas where policy and research actions are needed to advance positive change on population health and wellbeing. We highlight empirical evidence of drivers within the EU guided by the activities within the thematic Action Groups of the European Innovation Partnership on Active and Healthy Ageing (EIP on AHA), focusing on Lifespan Health Promotion & Prevention of Age-Related Frailty and Disease (A3 Action Group). We will specifically focus on the effect of Culture on Health, highlighting cross-cutting drivers across domains such as innovations at the individual and community level, and in synergies with business, policy and research entities. We will present examples of drivers for creating a Culture of Health, the barriers, the remaining gaps, and areas of future research to achieve an inclusive and sustainable asset-based community.